Permanência na pós-graduação durante a pandemia e os impactos posteriores aos estudantes - Rodrigues, Valentim Heleno Santos (2024)
The Covid-19 pandemic worsened the situation of students remaining in higher education and postgraduate studies, as the problems that led to student dropout intensified, thus contributing to a decrease in the number of students studying and completing Higher Education in Brazil. This scenario of uncertainty and conflicts brought educational, social, financial and political impacts to the field of Higher Education, specifically Postgraduate Studies. The general objective of this research was to analyze the conditions of students' stay in the Postgraduate Program in International Relations/UEPB, during the pandemic, and the impacts reverberated after this period. The methodology adopted to support this academic research was based on a qualitative-quantitative study and documentary research regarding the stay at PPGRI/UEPB, during the post-pandemic period. Institutional actions were identified, developed during the pandemic process, that helped or hindered the students' permanence in the PPGRI/UEPB, as well as external factors that contributed to their permanence or evasion in the course during the pandemic, as well as being listed among the students. how possibilities were identified for improving institutional practices to promote the retention of students in postgraduate studies after the pandemic period. After identifying the issues arising in the research, as a technical product of this professional master's degree, a report was developed with a view to contributing to the development of postgraduate retention policies, specifically in the Postgraduate Program in International Relations/UEPB, aiming to identify internal problems and solutions to promote permanence.